Stress Physiology in Infancy and Early Childhood: Cortisol Flexibility, Attunement and Coordination. (August 2016) - Atkinson, L.; Jamieson, B.; Khoury, J.; Ludmer, J.; Gonzalez, A.
Abstract : Research on stress physiology in infancy has assumed increasing importance due to its lifelong implications. In this review, we focus on measurement of hypothalamic‐pituitary‐adrenal (HPA) function, in particular, and on complementary autonomic processes. We suggest that the measure of HPA function has been overly exclusive, focusing on individual reactivity to single, pragmatically selected laboratory challenges. We advocate use of multiple, strategically chosen challenges and within‐subject designs. By administering one challenge that typically does not provoke reactivity and another that does, it is possible to represent allostatic load in terms of "flexibility, " the capacity to titrate response to challenge. We also recommend assessing infant reactivity in the context of the primary caregiver's physiological function. Infant‐mother "attunement" is central to developmental psychology, permeating diverse developmental domains with varied consequences. A review of adrenocortical attunement suggests that attunement is a reliable process, manifest across varied populations. However, attunement appears stronger in the context of more highly stressful circumstances, such that administration of multiple, selected challenges may help evaluate the degree to which individuals titrate attunement to challenge and determine the correlates of this differential attunement. Finally, we advocate studying the "coordination" of HPA function with other aspects of stress physiology and variation in the degree of this coordination. The use of multiple stressors is important here because each stress system is differentially sensitive to different types of challenge. Therefore, use of single stressors in between‐subject designs impedes full recognition of the role played by each system. Overall, we recommend measure of flexibility, attunement, and coordination in the context of multiple challenges to capture allostasis in environmental and physiological context. The simultaneous use of such inclusive and integrative metrics may yield more reliable findings than has hitherto been the case. The interrelation of these metrics can be understood in the context of the adaptive calibration model..